TRAUMA REPRESENTATION IN AGUK IRAWAN’S KIDUNG RINDU DI TAPAL BATAS: A SIGMUND FREUD’S PSYCHOLOGICAL ANALYSIS - Afriliya, Novi; Alivardani, Eka Nova; Suaedi, Hasan (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This research aims to describe the representation of two forms of trauma, namely psychological trauma and neurosis trauma, in the novel Kidung Rindu di Tapal Batas by Aguk Irawan MN. This study integrates the traumatic theory of Fatmah K. and Diah Retno Ningsih with Sigmund Freud's psychoanalytic approach to interpret the psychological dynamics of the characters through three structures of personality: id, ego, and superego. This research uses a qualitative descriptive method through reading techniques and recording data in the form of dialogue, narration, and descriptions that show symptoms of trauma. The analysis is carried out by classifying the types of trauma and interpreting the characters' psychological responses to inner stress and traumatic experiences. The research results show that psychological trauma and neurosis are represented through inner conflict, fear, loss, and guilt experienced by the characters. The dynamics between the id, ego, and superego show how the ego acts as a mediator between instinctual drives and moral control in the face of traumatic stress. Theoretically, this research enriches the study of literary psychology by confirming that literary works function as a reflection of human psychological conditions and a medium for understanding the dynamics of trauma in the context of Indonesian literature.